COVERAGE OF KIDNAPPING IN NORTH-WEST NIGERIA:AN ANALYSIS OF DAILY TRUST AND THE GUARDIAN NEWSPAPERS - Salisu Mohammed, Amina (UI Scholars Hub, 2023)
The study examined the coverage of kidnapping in North-West Nigeria by looking at the extent of coverage, prominence and major sources of news found in the stories in Daily Trust and The Guardian newspapers for the period of two years using content analysis research design. The findings indicated little attention to the interpretative role of the mass media, low prominence and too much reliance on Government/official news sources in reporting kidnapping in North-West Nigeria. Keywords: Kidnapping, Terrorism, Insecurity, Coverage, Armed Banditry